QUALITY IMPROVEMENT OF TRADITIONAL COCONUT OIL WITH ADDITION OF PANDANUS ETHANOL EXTRACT (Pandanus amaryllifolius Roxb) - Muharnanti Muharnanti; Maherawati Maherawati; Suko Priyono (BPFP Faperta UNIB, 2020)
Traditional coconut oil is coconut oil that is produced for generations in a simple way. This coconut oil cannot last long without purifying. This oil is produced by heating so that the quality of the oil decreases. Improving the quality of thisoil can be done by adding extract of ethanol pandanus fragrant which is easily obtained and contains natural antioxidants. This study aims to determine the characteristics of traditional coconut oil after the addition of ethanolic extract of pandanus fragrant leaves. The study was conducted following a randomized block design (RBD) of one factor, namely the concentration of ethanol extract of pandanus leaves consisting of 6 levels of treatment, namely p1 = 0,00%, p2 = 0.02%, p3 = 0.04%, p4 = 0.06%, p5 = 0.08%, and p6 = 0.10% , with 4 replications. Data were analyzed by ANOVA test and further tests using BNJ test with a level of 5%. The results showed that the best treatment was obtained at the ethanol extract concentration of 0.10% pandanus fragrant leaves that produce coconut oil with a water content of 0.128%, free fatty acid content of 0.489%, and a saponification rate of 229.22 mg KOH/g of oil. The highest descriptive sensory characteristics of traditional coconut oil are yellowish green (4.48) and slightly pandanus (3.20)